2015
DOI: 10.1038/bjc.2015.250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pEGFR and pAKT as response-predictive biomarkers for RAS wild-type patients to anti-EGFR monoclonal antibodies in metastatic colorectal cancers

Abstract: Background:RAS wild-type (RASw/t) tumours have been associated with better outcomes in patients with metastatic colorectal cancer (mCRC) treated with anti-EGFR monoclonal antibodies (mAb). We investigated the expression of EGFR downstream proteins under their active phosphorylated forms as potential markers in response to these patients.Methods:One-hundred tumour samples were collected from patients with mCRC refractory to FOLFOX and/or FOLFIRI and treated by a combination of chemotherapy with anti-EGFR mAb. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Thus, patients with activated cell surface receptors (notably EGFR) and PI3K pathway are more likely to respond to anti-EGFR therapy. Our data confirm and extent previously reported observations on the predictive value of phospho-EGFR and phospho-Akt ( Van Schaeybroeck et al , 2005 ; Harle et al , 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, patients with activated cell surface receptors (notably EGFR) and PI3K pathway are more likely to respond to anti-EGFR therapy. Our data confirm and extent previously reported observations on the predictive value of phospho-EGFR and phospho-Akt ( Van Schaeybroeck et al , 2005 ; Harle et al , 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, in one of our previous studies, we presented in vitro data suggesting that a high level of activated EGFR is associated with a good response to cetuximab . Furthermore, several other studies have suggested that cells are sensitive to EGFR inhibition only if they are dependent on EGFR for Akt activation, cell survival, and growth . However, in this study, we could not find any correlation between EGFR and Akt activation or between Akt activation and cetuximab sensitivity.…”
Section: Discussioncontrasting
confidence: 85%
“…Recently, several investigators argued the possibility of personalized therapy by evaluating the specific signalling activation state of tyrosine kinases in different types of malignancies, including lung carcinoma [ 40 ], colorectal carcinoma [ 41 ] and ovarian carcinoma [ 42 ]. Most recently, we have reported that c-MET phosphorylation in clinical samples is a potential biomarker predicting response to a selective c-MET inhibitor for SS patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%